2021
DOI: 10.1016/j.matchemphys.2020.123909
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of k-Carrageenan-gelatin hybrid composite coating on the medical grade stainless steel (SS304) used as anticorrosive barrier

Abstract: Biopolymers derived from seaweed are good anticorrosive, antibacterial and anticancer agents. These biopolymers family includes the k-Carrageenan with good potential anticorrosive feature that is extracted from the red seaweed Acanthophora spicifera -Rhodophyceae. To obtain the best corrosion inhibition properties the k -Carrageenan hybrid composite with gelatin was prepared by sol-gel method. In the present study, two natural compounds have been used to prepare the proposed hybrid composite material. Such as,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The absorption peak at 3429 cm À1 and 3404 cm À1 attributed to N-H the absorption peak at 3429 cm À1 and 3404 cm À1 attributed to N-H stretching vibrations of amide group in gelatin reported by Muthulakshmi et al 2021. 18 These values are in agreement with those already reported for similar systems. [19][20][21]…”
Section: Ftir Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The absorption peak at 3429 cm À1 and 3404 cm À1 attributed to N-H the absorption peak at 3429 cm À1 and 3404 cm À1 attributed to N-H stretching vibrations of amide group in gelatin reported by Muthulakshmi et al 2021. 18 These values are in agreement with those already reported for similar systems. [19][20][21]…”
Section: Ftir Analysissupporting
confidence: 92%
“…The XRD patterns of the films based on sheep milk, gelatin, and casein are presented in Figure 2. From Figure 2, it is evident that while the patterns of sheep milk and casein films had two sharp peaks each, those corresponding to gelatin are F I G U R E 1 FTIR spectrum peaks of casein, gelatin 18 and sheep milk powderbased biocomposite films not well defined. The peaks of sheep milk film appeared at 2θ = 34.8 and 42 .…”
Section: Xrd Analysismentioning
confidence: 99%
“…This method involves preparing a film‐forming solution, spreading the prepared solution on smooth plates, such as polytetrafluoroethylene or glass plates, and evaporating the solvent after cooling [54]. For example, films made of carrageenan compounded with sodium alginate [55], gelatin [56, 57], konjac glucomannan [58, 59] and starch [60, 61] can be made by this method. This method has the advantages of low cost and simple operation, but it requires a long drying time; additionally, the film properties are significantly affected by ambient temperature, humidity and solution concentration.…”
Section: Preparation Methods and Mechanization Of Carrageenan Wrapsmentioning
confidence: 99%
“…Roy et al added carbon dots to carrageenan/gelatin films for food packaging and found a reduced surface roughness for most combinations with carbon dots as compared to the pure carrageenan/gelatin films [ 140 ]. Muthulakshmi et al used AFM topography images to show the improved corrosion resistance of a medical-grade stainless steel in mild acidic conditions due to a carrageenan/gelatin coating [ 141 ]. Similarly, Souza et al investigated the topography of a κ-carrageenan multilayer coating with quercetin-loaded lecithin/chitosan nanoparticles and found a higher roughness for the quercetin nanoparticle layers than for the κ-carrageenan layers [ 142 ].…”
Section: Applicationsmentioning
confidence: 99%